PEMANFAATAAN BIOCHAR SEBAGAI BAHAN PEMBENAH TANAH PADA POKTAN MEKAR SARI II KECAMATAN SUNGAI KAKAP - Suryani, Rini; Sutikarini, Sutikarini; Masulili, Agusalim (Jurnal Abdi Masyarakat, 2023)
PKM is purposed to help the Mekas Sari II farmer group, Sungai Kakap District, Kubu Raya Regency to be able to maintain the quality of their land by using biochar which is processed from coconut harvest waste, which in turn is expected to have an impact on increasing production. The specific targets achieved are: 1) increasing the knowledge and skills of partner farmers in the manufacture of biochar from coconut waste. 2) increasing knowledge and skills of partner farmers in applying harvested waste biochar as a soil amandemen. The method of PKM activities for the Mekar Sari II Group, Sungai Kakap Subdistrict, are: 1) counseling on the use of harvested waste biochar as a soil improvement agent. 2) training in the production of biochar from coconut harvest waste using a simple method. 3) make demonstration plots for coconut harvesting applications. The results of the PKM activity show that the use of biochar from coconut harvest waste as a soil improvement material has the potential to be developed. This is because the potential of coconut waste has not been utilized optimally. After carrying out Community Service activities, the Mekar Sari II Farmer's Group, Sungai Kakap District, Kubu Raya Regency, there was an increase in both affective (knowledge), cognitive (attitude) and skills in the use of harvested waste as soil improvement material to increase the production of plants.